EFFECTS OF REPETITIVE EMPLACEMENT OF BASALTIC INTRUSIONS ON THERMAL EVOLUTION AND MELT GENERATION IN THE CRUST - Annen C.; Sparks R.S.J. (My University, 2002)
A one-dimensional thermal conduction model simulates the repetitive intrusion of basalt sills into the deeper parts of the crust. The model assumes geothermal gradients of 10-30°C km-1, and intrusion depths at 20 and 30 km. A range of intrusion rates from 50 m of intruded basalt every 1000, 10#000 and 100#000 years cover a range of geodynamic situations. There is an initial incubation period in which the basalt intrusions solidify. Generation of silicic melts initiates when the solidus temperatures of either the basalt magma or surrounding crust is reached. At an intrusion rate of 50 m per 10#000 years incubation periods in the range 105-106 years are estimated, consistent with geochronological and stratigraphic data on many volcanic systems where there is commonly an evolution from mafic to silicic volcanism. Melt generation involves simultaneous cooling and crystallization of intruding basalt and partial melting of both new basaltic crust and pre-existing old crust. The proportion of these components depends on the fertility of the crust, in particular the abundance of hydrous minerals, and the temperature and water content of the basalt magma. For a wet (2% H2O) and cool (1100°C) basalt, melt generation can be dominated by residual liquids from basalt crystallization. For a dry (0.3% H2O) and hot (1300°C) basalt emplaced into fertile crustal rocks, such as pelite, melt generation can be dominated by partial melting of old crust. Melt proportions and temperature vary greatly across such a deep crustal intrusion zone, resulting in geochemical diversity in magmas. Segregated melts, if mixed together during ascent or in a high-level magma chamber, will be geochemical hybrids with mantle and crustal components. Intrusion rates of 50 m per 100#000 years or less are too low for large-scale melt generation in the crust. Periods of magmatic intrusion create reverse geothermal gradients and thermal anomalies in the crust which will take several million years to decay. Such anomalous zones are predisposed to remelt if a subsequent magmatic episode initiates.
Keywords: INTRUSIONS; BASALTS; RESIDUAL MELTS; ANATEXIS; HEAT TRANSFER